Controlling floods and droughts through underground storage: from concept to pilot implementation in the Ganges River Basin - Pavelic, Paul; Brindha, Karthikeyan; Amarnath, Giriraj; Eriyagama, Nishadi; Muthuwatta, Lal P.; Smakhtin, Vladimir U.; Gangopadhyay, Prasun K.; Malik, Ravinder Paul Singh; Mishra, Atmaram; Sharma, Bharat R.; Hanjra, Munir A.; Reddy, R.V.; et al. (International Water Management Institute, 2015)
The concept of ‘Underground Taming of Floods for Irrigation’ (UTFI) is introduced as an approach for co-managing floods and droughts at the river basin scale. UTFI involves strategic recharge of aquifers upstream during periods of high flow, thereby preventing local and downstream flooding, and simultaneously providing additional groundwater for irrigation during the dry season for livelihood improvement. Three key stages in moving UTFI from the concept stage to mainstream implementation are discussed. An analysis of prospects in the Ganges River Basin are revealed from the earliest stage of mapping of suitability at the watershed level through to the latest stages of identifying and setting up the first pilot trial in the Upper Ganges, where a comprehensive evaluation is under way. If UTFI can be verified then there is enormous potential to apply it to address climate change adaptation/mitigation and disaster risk reduction challenges globally.